Post-translational modification of RNA m6A demethylase ALKBH5 regulates ROS-induced DNA damage response. Issue 10 (28th May 2021) - Yu, Fang; Wei, Jiangbo; Cui, Xiaolong; Yu, Chunjie; Ni, Wei; Bungert, Jörg; Wu, Lizi; He, Chuan; Qian, Zhijian
Abstract: Faithful genome integrity maintenance plays an essential role in cell survival. Here, we identify the RNA demethylase ALKBH5 as a key regulator that protects cells from DNA damage and apoptosis during reactive oxygen species (ROS)-induced stress. We find that ROS significantly induces global mRNA N 6 -methyladenosine (m 6 A) levels by modulating ALKBH5 post-translational modifications (PTMs), leading to the rapid and efficient induction of thousands of genes involved in a variety of biological processes including DNA damage repair. Mechanistically, ROS promotes ALKBH5 SUMOylation through activating ERK/JNK signaling, leading to inhibition of ALKBH5 m 6 A demethylase activity by blocking substrate accessibility. Moreover, ERK/JNK/ALKBH5-PTMs/m 6 A axis is activated by ROS in hematopoietic stem/progenitor cells (HSPCs) in vivo in mice, suggesting a physiological role of this molecular pathway in the maintenance of genome stability in HSPCs. Together, our study uncovers a molecular mechanism involving ALKBH5 PTMs and increased mRNA m 6 A levels that protect genomic integrity of cells in response to ROS.